The Architecture of Concepts : The Historical Formation of Human Rights - Bolla, Peter de (Book collections on Project MUSE., 2013)
The Architecture of Concepts proposes a radically new way of understanding the history of ideas. Taking as its example human rights, it develops a distinctive kind of conceptual analysis that enables us to see with precision how the concept of human rights was formed in the eighteenth century. The first chapter outlines an innovative account of concepts as cultural entities. The second develops an original methodology for recovering the historical formation of the concept of human rights based on data extracted from digital archives. This enables us to track the construction of conceptual arch.